Penerapan Program Kredit Usaha Rakyat Bank Syariah Indonesia dalam Meningkatkan Pendapatan UMKM di Kota Padang - Irsadunas; Adif, Riandy Mardhika (SAFE-Network, 2024)
The aim of this research is how much the people's business credit program has increased the income of MSMEs in Padang City. People's Business Credit (KUR) is one of the government's initiatives to develop the MSME industry, especially to support obtaining financing through the People's Business Credit (KUR) program. The micro and MSME development program initiated by the government is now known as People's Business Credit. Furthermore, the relevance of the role of sharia banking in global economic and financial dynamics. Furthermore, this research also determines the impact on the economy of the people of Padang City from the KUR program provided by BSI, providing sustainability or development so that it is worthy of being a strategy to improve the economy of the local community. This research uses qualitative research methods combined with a library research approach. The data sources used in this research are primary data sources and secondary data sources. The data collection technique used in this research is an information search technique using observation of the sources used in the research, structured interviews with sources related to the subject matter, document collection studies, as well as primary and secondary documents. Data analysis begins with collecting data, then comparing, categorizing, and looking for themes to interpret the data. The results of this research show that the implementation of BSI KCP Padang People's Business Credit (KUR) financing has many advantages, one of which is an easy and fast application method and disbursement time, no fines for late payments, cheaper installments so as to save customers' expenses. In this way, KUR BSI KCP Padang financing can increase the income of MSMEs in Padang City.